2020
DOI: 10.1177/1076029620925910
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Management of Anticoagulation in the Periprocedural Period App Into an Electronic Health Record: A Prospective Cohort Study

Abstract: Appropriate perioperative management of patients on chronic oral anticoagulation (OAC)—including warfarin and the direct oral anticoagulants—is a poorly defined yet important clinical issue with potentially severe consequences in the postoperative period. We sought to prospectively evaluate the effect of the Management of Anticoagulation in the Periprocedural Period (MAPPP) mobile app as a clinical decision tool in the management of patients on chronic OAC undergoing elective procedures or surgeries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…The study revealed that physicians are more likely to follow the guidelines provided by the app with younger patients with normal renal function and who are taking DOAC medication, whereas they tend to trust their clinical expertise and deviate from the guidelines with older patients with impaired renal function and who are receiving warfarin therapy. The study showed a significantly lower rate of admissions to the emergency department for the cohort in which health practitioners accepted the app’s advice than in the cohort where the advice was rejected (4.0% vs 8.3%; P =.02) [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study revealed that physicians are more likely to follow the guidelines provided by the app with younger patients with normal renal function and who are taking DOAC medication, whereas they tend to trust their clinical expertise and deviate from the guidelines with older patients with impaired renal function and who are receiving warfarin therapy. The study showed a significantly lower rate of admissions to the emergency department for the cohort in which health practitioners accepted the app’s advice than in the cohort where the advice was rejected (4.0% vs 8.3%; P =.02) [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…An SF-12 survey was sent to eligible patients who had previously participated in our prospective cohort regarding the effectiveness of the MAPPP app. 6 The study was approved by the health system Institutional Review Board (IRB#:18-0948) overseeing all hospitals and healthcare facilities visited by the patients and was conducted in accordance with principles of the Declaration of Helsinki. Informed consent forms were given to all patients who were invited to complete the survey.…”
Section: Methodsmentioning
confidence: 99%
“… 8 10 The participants were separated into two groups depending on whether their healthcare providers had previously decided to accept the app's treatment recommendations (acceptance group) or not (rejection group), based on the patient cohorts previously defined. 6 The total number of 30-day hospital readmissions of the responders was used to calculate the related costs for each group. These costs and the resulting quality-of-life (QOL) data were used to calculate the incremental cost-effectiveness ratio (ICER).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…40,41 In preparing for these discussions, it may be helpful to collect examples of successful initiatives from other institutions, particularly from those that utilize the same EHR. [42][43][44] These examples may come from published medical literature (perhaps previously collected in Section 2.3 above), EHR vendor-based libraries, or direct correspondence with staff at other institutions. While IT services may be perceived as barriers to implementation, this preparation can enhance collaboration and even reduce the implementation budget by providing explicit guidance for the design and construction of EHR tools.…”
Section: Health Information Technology (It) Departmentmentioning
confidence: 99%